Hydrothermal synthesis and photocatalytic properties of CuGaO2/ZnO hexagonal platelet hybrids. (May 2019) - Choi, Min Uk; Hayakawa, Tomokatsu
Graphical abstract: Highlights: Hexagonal-platelet delafossite CuGaO2 particles were synthesized by a hydrothermal method. The surface of platelet CuGaO2 could be used to create hybrids with n-type ZnO semiconductors. The optical band-gap energy and photocatalytic properties were investigated. The annealed CuGaO2/ZnO hybrids displayed a better performance as photocatalysts. Abstract: Delafossite CuGaO2 as a p-type semiconductor is classified as a wide band-gap semiconductor owing to direct transitions on the high energy side. Solid state reaction and sol-gel synthesis are applicable as traditional methods for synthesizing delafossite CuGaO2 . However, both synthesis methods require high temperatures, and the sol-gel method additionally requires a nitrogen gas atmosphere. In this study, hexagonal-platelet CuGaO2 is synthesized using a hydrothermal method, which can also be adapted to the synthesis of the CuGaO2 /ZnO hybrids. As a result, it was found that the surface of platelet CuGaO2 particles could be used to create hybrids with n-type ZnO semiconductors. This paper also presents the optical band-gap energy and photocatalytic properties of hexagonal-platelet CuGaO2 and CuGaO2 /ZnO hybrids.